THE PERFORMANCE OPTIMIZATION ANALYSIS OF INSPECTORATES SUPERVISION FUNCTIONS REGIONAL DEVICE ORGANIZATION AT SUKABUMI REGENCY - KUSNADI; DARMO H SUWIRYO; ACEP SAMSUDIN (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2021)
This research was conducted at the Sukabumi Regency Inspectorate with a study on Optimizing the Performance of Sukabumi Regency Inspectorate Employees in Carrying out Work Supervision Functions in Regional Organizations in the Sukabumi Regency Environment. This research started from the finding that several medium-term strategic goals were not achieved in the process of completing the work supervisory function which became an indicator that performance in 2016 to 2020 was not achieved optimally, so efforts were needed to support the optimization of employee performance in carrying out the work supervisory function. The informants in this study were employees of the Sukabumi Regency Inspectorate who were directly involved with the system to be analyzed by the researcher, so the number of informants who were deemed worthy were 11 informants. To approach this problem, use the theory of Prwirosento in Edy Sutrisno. This research is a qualitative descriptive study. The data used in this study are primary data obtained from direct interviews of all employees involved in the implementation of the Work Supervision Function. Data collection techniques using interview techniques, observation and documentation. Then do the data analysis and translate the data obtained from the data that has been selected, and then draw conclusions. The results of this study can be concluded that: first, the results of the study indicate that the supervision carried out by the Regional Inspectorate of Sukabumi Regency has not reached maximum supervision because it is hampered by the vastness of the Sukabumi Regency area, the lack of human resources, the uneven ability of employees, the uncooperativeness of the regional organizations when asked for information, , The lack of communication carried out by the leadership of regional organizations when facing problems that occur in the field. The two efforts were made to overcome these obstacles by increasing the number of experts, increasing the ability of employees through training, building positive communication with all regional organizational leaders, and changing the paradigm of supervision to become more friendly